Single Axis Automatic Solar Tracking System Using Microcontroller - Soumya Das; Pradip Sadhu; Nitai Pal; Suprotim Mukherjee (Institute of Advanced Engineering and Science, 2014)
Solar power generation had been employed as a renewable energy for years ago. Residents that uses solar power as their alternative power supply will bring benefits to them. The main objective of this paper is to develop a microcontroller-based solar panel tracking system which will keep the solar panels aligned with the Sun in order to maximize in harvesting solar power. When the intensity of light is decreasing, this system automatically changes its direction to get maximum intensity of light.Light dependent photo resistors are used as the sensors of the solar tracker. For rotating the appropriate position of the panel, a steper motor is used. This design is covered for a single axis and is designed for residential use. Finally, the project is able to track and follow the Sun intensity in order to get maximum power at the output regardless motor speed. http://dx.doi.org/10.11591/telkomnika.v12i12.6742